Pengaruh Arus Terhadap Struktur Mikro Dan Sifat Mekanik Produk Las Tembaga Dan Baja Karbon Dengan Metode Tungsten Inert Gas (TIG) - Hermawan, Mawan; , Tri Widodo Besar Riyadi, ST, MSc, Ph.D (2015)
This research is to unveil the chemical composition, micro structure and hardness value on metal used on TIG welding and also to unveil the current effect used toward the quality of welding product. The materials used are copper and carbon steel alloy with the thickness of each is 5 mm. The welding is performed using TIG welding method (Tungsten Inert Gas) with a single V seam and the current variations are 70 A, 75 A, 80 A, 85 A, 90 A and 20 - 30 V voltage and 8 - 12 cm/min of shear rate. The tests performed are chemical composition test, micro structure test and hardness test (Vickers). Research results show that current variation affects toward micro structure and hardness value significantly. What happened on micro structure of steel material is phase of ferrite and paerlite because on welding that using the highest air cooling and hardness value is acquired on 90 A current which is base metal 33.95 HVN, HAZ 42.36 HVN and 44.53 HVN welding metal. While what is seen on the copper material micro structure seen is the highest which are Cu and Zn element and if current given is getting bigger, then the hardness value is actually decreasing and the highest hardness value is acquired on 70 A current which is 19.57 HVN, HAZ 18.96 HVN metal base and 18.62 HVN welding metal. Keywords: TIG welding, current, copper, carbon steel, hardness